Formulasi faktor kualiti bagi permarkahan lukisan kejuruteraan - Yuwaldi Away,; Zarina Shukur,; Mohd Juzaidin Abdul Aziz,; Mohammad Asmady Dawari, (2003)
This work describes the design and implementation of an instrument for assessment that would enable Mechanical Engineering Drawing (MED) to be evaluated automatically by using the computer. A prototype of the Computer- Aided Marking System For Engineering Drawing System (CAMSEDS) could ~place the existing manual marking process. The CAMSEDS framework begins from the display of objects that are generated from the lecturers' and earners' AutoCAD 2000 drawings that have been changed into the DXF files. The geometrical data are extracted and analyzed by comparing geometrical rata from the lecturer's and the learner's drawing automatically or a semi- automatically for similarities and differences between them. In CAMSEDS, the empirical data is compared in order for the system to automatically evaluate based on the following criteria: drawing entity, the entity of object accuracy and the accuracy of measurement. The semi-automatic analysis also involves manual assessment to evaluate the accuracy of a design based on visual I how that CAMSEDS prototype would help in reducing marking errors, in comparison to the present manual assessment via computerized MED. The formulas for quantitative assessment that have been proven effective in making CAMSEDS assessment more relevant and consistent are (1) formulation of assessment for drawing entity (2) formulation of assessment for the entity of object accuracy. (3) formulation of assessment for the accuracy of measurement, and (4) formulation of assessment for visualition